Elephantopus Scaber Linn. - Phytochemical Evaluation - Nair, Aswathy V; Ansary, P Y; Oommen, Sara Monsy; Shincy , Mol V V (International Research Journal of Ayurveda & Yoga, 2021)
Anachuvadi (Elephantopus scaber Linn.) is a perennial herb which was used to treat various conditions such as wounds, headache, insomnia, skin diseases, conjunctivitis, and mouth ulcer by the Ayurvedic physicians of Kerala. Horthus malabaricus by Van Rheede describes its use in mental disorders especially depression. In order to validate the traditional claim the preliminary phytochemical analysis of the drug was carried out. The preliminary phytochemical analysis aims at analysing the physiochemical property of drugs, their qualitative analysis, ash values, extractive values, moisture and volatile contents, estimation of Tannins and Phenols. On analysing the phytochemical constituents present in the crude drug, the drug revealed the presence of alkaloids, flavonoids, saponins, carbohydrates, proteins, phenols, steroids, and tannins. These phyto-constituents present in the drug may be responsible for the therapeutic potential of the drug. Apart from the findings of previous research works, qualitative analysis of ash was conducted to check the presence of acid and basic radicles. Extractive values were determined for Successive solvent extraction of choorna (powder) of whole plant in solvents like petroleum ether, cyclohexane, acetone and alcohol. These findings will help to ensure the genuineness, quality and purity of the drug.